Le “ Quartier des Chrétiens ” (Maḥallat al-Naṣârâ) de Damas au milieu du xviiie siècle (1150-1170/1737-1757) - Brigitte Marino (Revue des Mondes Musulmans et de la Méditerranée)
Located in the north-eastern sector of the intramural city of Damascus, the “ Quarter of the Christians ” (Maḥallat al-Naṣârâ) was, in the Ottoman period, the privileged place of residence of the Christians in Damascus, with, to a lesser extent, other quarters located in the suburbs of the city. Studying a series of real estate transactions carried out between 1737 and 1757 by Christians and Muslims, one examines here the architectural specificity of the houses located in this quarter and the cohabitation between Christians and Muslims. Compared to the suburb of Mîdân, for which we have similar data for the same period, the houses of Maḥallat al-Naṣârâ were characterized by their high value and the significant number of their rooms. The Christians, who were the majority of the inhabitants in this quarter, seemed to express, more than the Muslims, their will to set up here for a long time. Some mosques were to be found in this quarter but the houses of the Muslims seemed to be relatively modest: the luxurious residences were owned amost exclusively by Christians.